Monitoramento do desenvolvimento de colônias de Abelhas africanizadas sobre a influência do sol e sombra na região semiárida do nordeste brasileiro (Mossoró -RN) - Sombra, Daiana da Silva (Universidade Federal Rural do Semi-Árido, 2013)
This study aimed to assess the the effect of direct sunlight and shade in two groups of AHB colonies. Sheets of carnauba trees were used to provide shading for a group of hives and as control another group of hives were installed direct under the sun. The experiment was conducted at the Technology Center of Beekeeping and Meliponiculture of Rio Grande do Norte, at the Experimental Station of UFERSA, Mossoró-RN. 16 Langstroth beehives were used, 8 in the shade and 8 under the sun. During the period from April, 05, 2012 to March 18, 2013 were performed monthly monitoring and about the development of the colonies. Approximatelly every 10 days the survey was conducted with data collected in % in the areas of oviposition (eggs laying by queens) ,open brood, capped brood, honey and pollen. The data were tested for normality, analysis of variance based on the least squares method and the comparison of means was done by Tukey test with 5% level of significance The environment showed an influence upon duration or longevity of colonies with difference statistically significant (P <0.01), with an average duration of 132 days in the sun and 155 days in the shade. During the experiment, the colonies had 65% reduction in bee populations in the shade and 90% under the sun. There were no statistical differences between the groups as oviposition, open brood and capped brood. The area of honey was higher in the colonies under the sun and pollen area was higher in shadow environment, both differences statistically significant (P<0,01). The drought of 2012, the most serious in the last 50 years in the Brazilian Northeast, had an important impact on both groups of colonies but the AHB colonies had a better adaptation in the shadow than under the sun in the semiarid Northeast region. Honey production accumulated in the colonies supers installed in the shade was approximately 45% higher than under the sun. It was found that bees (AHB) have a better adaptation to the environment under the shadow of the sun in the semiarid Northeast
Monitoring of the development of colonies of africanized honey bees under the influence of sunligth and shade in the semiarid region of northeast of Brazil (Mossoró-RN)
Keywords: Apis mellifera; temperature; honey; pollen; brood; Apis mellifera; Temperatura; Mel; Pólen; Crias; CIENCIAS AGRARIAS::MEDICINA VETERINARIA